Emergency medicine diagnosis and management - Brown, Anthony F. T.; Cadogan, Michael D. (CRC Press, 2021)
The eighth edition of this international bestselling emergency medicine handbook has been completely revised and updated to include the latest evidence-based guidelines and treatment protocols underpinning best practice in emergency medical care. Carefully designed to suit the needs of interns and resident doctors working in the emergency department as well as specialist trainees, the book covers the full range of emergencies - general medical, infectious disease and foreign travel-related, toxicological, surgical, paediatric, obstetric and gynaecological, ophthalmic and psychiatric - as well as practical procedures and administrative and legal issues.